Breakthroughs in groundnut production communities in Nigeria - Akpo, E.; Ojiewo, Christopher Ochieng; Omoigui, L.O.; Rubyogo, Jean-Claude; Varshney, Rajeev K. (Springer, 2020)
Mrs. Hadja Talatu Idrissa (Fig. 6.1), a community women leader, is the chairperson of the Bunkure women group that is active in groundnut production and oil processing. The group which counts 25 members joined the TLIII project family 4 years ago. They started growing a small seed pack of 5 kg in their community farmland. “It was the harvest of this seed pack that we revolved and planted in a bigger farm plot in the following year,” reported Mrs. Hadja.